2005
DOI: 10.1165/rcmb.2005-0103oc
|View full text |Cite
|
Sign up to set email alerts
|

Bone Morphogenetic Protein Receptor Type II C-Terminus Interacts with c-Src

Abstract: Mutations of bone morphogenetic protein receptor type II (BMPR-II) have been associated with familial and idiopathic pulmonary arterial hypertension (PAH). BMPR-II is a member of the transforming growth factor-␤ receptor superfamily. It consists of extracellular, transmembrane, and kinase domains, and a unique C-terminus with mostly unknown function. However, a number of PAH-causing mutations are predicted to truncate the C-terminus, suggesting that this domain plays an important role in the homeostasis of pul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
90
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(94 citation statements)
references
References 43 publications
4
90
0
Order By: Relevance
“…Critical regulatory elements in the Id1 promoter include a BMP-responsive region, a serum-responsive region, and a region associated with constitutive expression in breast cancer cells (14)(15)(16)34). Consistent with previous data from noncancerous cells, the present study implicates the crosstalk of Src tyrosine kinase signaling with the BMP-Smad pathway as an additional regulator of Id1 expression in cancer (42)(43)(44)(45). Importantly, this was also associated with a substantial diminution in invasion.…”
Section: Discussionsupporting
confidence: 89%
“…Critical regulatory elements in the Id1 promoter include a BMP-responsive region, a serum-responsive region, and a region associated with constitutive expression in breast cancer cells (14)(15)(16)34). Consistent with previous data from noncancerous cells, the present study implicates the crosstalk of Src tyrosine kinase signaling with the BMP-Smad pathway as an additional regulator of Id1 expression in cancer (42)(43)(44)(45). Importantly, this was also associated with a substantial diminution in invasion.…”
Section: Discussionsupporting
confidence: 89%
“…The second regulator of STAT3 activation is the Src pathway [58]. Src has been shown to be implicated in PAH [5,31] and in the activation of STAT3 in human PAH-PASMCs [5]. Although the implication of Src in STAT3 activation in human PAH-PASMCs has not been reassessed in the present study, we showed that Src is activated in the distal pulmonary arteries of both MCT and sugen rats, confirming our previous findings in humans.…”
Section: Pulmonary Vascular Diseasesupporting
confidence: 90%
“…PLB reverses the activation of pathophysiological pathways affected by the activation of the STAT3/NFAT axis In PAH-PASMCs, STAT3/NFAT-mediated proliferation [4,31] has been linked with the downregulation of voltage-gated K + (Kv) channels [32,33], resulting in membrane depolarisation [31,33], the opening of voltage-dependent calcium channels, and an increase in [Ca 2+ ] i [4,31,34]. Using whole-cell patch clamping, we demonstrated that PLB (48 h) restores the decrease in total K + current density observed in PAH-PASMCs ( fig.…”
Section: Plb Decreases the Stat3/nfat Axis Activation In Pahpasmcsmentioning
confidence: 99%
“…These analyses suggest that the penetrance may be determined by subtle genetic differences in the known HPAH pathways, in particular the G-proteincoupled receptor pathways because that pathway was present in the final signature and in the GSEA. These findings are not surprising because G protein-coupled receptors have been implicated in pulmonary vasoconstriction pathways in several studies (28)(29)(30)(31)(32)(33)(34)(35).…”
Section: Discussionmentioning
confidence: 78%